Attention bias for appearance words can be reduced in women: Results from a single-session attention bias modification task. (December 2018) - Allen, Lydia; Mulgrew, Kate E.; Rune, Karina; Allen, Andrew
Abstract: Background and Objectives: We tested whether a single-session of attention bias modification (ABM) could change bias towards appearance-related words and improve body satisfaction. Methods: Females ( N = 102; M age = 33 years) completed an ABM session where attention was trained towards positive appearance-related information ( n = 31), away from negative appearance-related information ( n = 37), or a non-training session ( n = 34). Importance of appearance and shape concern were examined as moderators. Results: ABM was effective in women high on appearance importance, trained to direct attention away from negative appearance words. Limitations: No long-term follow up of attention biases or body image challenge were conducted. Conclusions: These findings suggest that certain types of attention biases are amenable to change within a single session. Highlights: Single session ABM reduced bias for negative appearance words. Result only for women high on appearance importance in Away Negative condition. No effect for Towards Positive or Neutral training or across body dissatisfaction.